Manastırlı Sâlih Fâik ve Dîvânı - Çambel, Şebnem (My University, 2019)
19. yy. şairlerinden biri olan ve 1835-1899 yılları arasında yaşayan Manastırlı Sâlih Fâik Bey, bulunduğu dönemin önemli şairlerinden biridir. Ailesi ve eğitimi hakkındaki bilgilerimiz sınırlı olmakla birlikte yaşadığı süre boyunca almış olduğu mühim memûriyet vazifeleri ile alakalı pek çok bilgiye ulaşılmıştır. Nakşibendî tarîkatinin Hâlidî koluna bağlıdır. Yaptığımız bu çalışmanın giriş kısmında Fâik Beyʼin de içinde olduğu Encümen-i Şuarâ hakkında bilgi verilmiştir. Birinci bölümde Fâik Beyʼin hayatı, edebî şahsiyeti ve eserlerinden bahsedilmiştir. İkinci bölümde ise İstanbul Üniversitesi Nadir Eserler Kütüphanesiʼnde bulunan ve tek nüsha olan Dîvânʼı şekil ve muhtevâ açısından incelenmiştir. Ayrıca bu kısımda Fâik Beyʼin aynı dönemde yaşadığı ve etkilendiği Osman Şems Efendi Dîvânı ile kısa bir karşılaştırma yapılmıştır. Son bölümde ise Dîvânʼın metni transkripsiyonlu olarak çalışmamıza eklenmiştir.

One of the poets in the 19th. century and lived between 1835 and 1899, Cenobite Mr. Sâlih Fâik, was one of the most important poets in the years he lived. Although we have limited information about his education and his parents, we could be able to reach pretty much information about important official duties that he got roled during his life. He dedicated himself to the dervish order of Nakşibendî branch which was Hâlidî. In the introduction section of this study, information about Encümen-i Şuarâ where Mr. Fâik being a member of has been given. In the first chapter; life, literary personality and works of Mr. Fâik has been mentioned. In the second chapter; Dîvân written by Mr. Faik and which we could be able to find as a single edition at The Nadir Eserler Library of The University of Istanbul has been analyzed according to its matter and content. Also in this chapter, there has been a short comparison made with the Dîvân written by Master Osman Şems lived in the same period of time and influenced by. In the last chapter, this Dîvân text which was hand written work has been added to our study as transcriptioned.
Keywords: Divan; Dîvân; Encumen-i Suara; Encümen-i Şuarâ Manastirli Salih Faik; Manastırlı Salih Faik